Computational modeling of pulverized coal fired boilers - Ranade, Vivek V.; Gupta, Devkumar F. (CRC Press, Taylor & Francis Group, 2015)
Computational Modeling of Pulverized Coal Fired Boilers successfully establishes the use of computational modeling as an effective means to simulate and enhance boiler performance. This text factors in how computational flow models can provide a framework for developing a greater understanding of the underlying processes in PC boilers. It also provides a detailed account of the methodology of computational modeling of pulverized coal boilers, as well as an apt approach to modeling complex processes occurring in PC boilers in a manageable way.